Juvenile Innovative Entrepreneurs: Challenges Pave A Path to Opportunities - LEELAVATHI, DR.D.; M, DR REVATHI; INDUMATHY, DR.R.; RAMACHANDRAN, DR.S.; SARAVANAN, K.; RAJ, DR. K. BHAVANA (The journal of contemporary issues in business and government, 2021)
Introduction: Young entrepreneurs loving to sharpen up their business skills and their business challenges pave a way to innovative ideas in business domain. It leads to develop a positive outlook among juvenile innovative entrepreneurs to utilize it as an opportunity. All effective innovations are breathtakingly. Youth entrepreneurship has becoming a vital factor in ensuring a brighter future for the nation. Entrepreneurship attitude leads to innovation is seen as not only the solution to unemployment but also fundamental in nurturing young people to unleash their potential to the fullest. Objectives: To emphasize the opportunities and challenges of budding entrepreneurs in the college students; and to identify the strategies of online free enterprises with nominal investment in Chennai City. Methods: Structured questionnaire package that inquired information including Gender, Age, Education level, Source of Parental Income, daily time spent for business and challenges leads to innovative business opportunities among young entrepreneurs. Liker’s five-point scale is developed to test the juvenile innovative entrepreneurs’ attitudes with percentage analysis and Chi- Square, KMO coefficient and the Bartlett’s test of with sixty samples for the research. Result: There is no significant relationship between “Challenges and Opportunities of Young innovative entrepreneurs. On the differing, the null hypothesis is accepted and shows that the there is significant relationship between “Challenges and Opportunities of Young innovative entrepreneurs during their business passion. Conclusion: The study assessed that young innovative entrepreneurs are using technology as a vast weapon to encounter the challenges faced while playing entrepreneurial role in the modern business world. “Most significant walk has to be taken by young innovative entrepreneurs to trendy economic revolution and cost-effective business strategy in the modern epoch.”